DIGITAL MEDIA LITERACY AND SOCIAL MEDIA COMPETENCE AMONG MILLENNIALS FOR TOURISM PROMOTION DURING THE COVID PANDEMIC - Restaty, Santa Margaretha Niken; Wuryanta, AG Eka Wenats (Interaksi: Jurnal Ilmu Komunikasi, 2022)
This research started with the fall issue of tourism at a time when the pandemic strikes Indonesia. Much effort has been made to try to explore the possibility of a revival of Indonesian tourism. The millennial generation has the advantage of digital capabilities that can encourage tourism revival through social media. This study aims to find out to what extent the level of social media literacy can be a factor that encourages the participation of the younger generation, especially millennials, in helping the level of tourism promotion in Indonesia. The methodology used is quantitative with data collection using questionnaires. The population is Paramadina Univ students and Mercu Buana Univ students. The analysis used is frequency tables, correlation tests, and factor analysis. The essential findings obtained are that the generation is relatively high in the context of digital media literacy, and there are three supporting factors in the framework of involvement in tourism promotion, namely the ability to process digital media production, social collaboration capabilities, and the consistency of the millennial generation in developing social media production patterns.